Corruption And Its Influence On The Society - Sultanovna, Khajiyeva Maksuda (The journal of contemporary issues in business and government, 2021)
In this article, we will focus on the socio-philosophical aspects of corruption, as well as an analysis of the results of our survey, which aims to identify views on corruption in society. This article is based on the methods of analysis, synthesis, statistical, comparative analysis, the results of the survey are based on statistical analysis, interpreted by diagrams and graphs.